Jewish Ethical Themes That Should Inform the National Healthcare Discussion: A Prolegomenon - Levin, Jeffrey S. (Journal of religion and health, 2012)
Despite the passage of H.R. 3590 in the 111th Congress, the national healthcare debate in the United States continues, with repeal or modification of the Patient Protection and Affordable Care Act under ongoing consideration. Reference is often made to morality or ethics, but typically in general terms only. This paper elucidates themes from one system of moral theology, namely Jewish healthcare ethics, that would valuably inform this debate. Themes include "covenant," "holiness," "justice," "mercy," "for the sake of peace," "to save a life," "peoplehood," "repair of the world," "repentance," and "jubilee." Policy-related, economic, political, and moral challenges to acting on these principles are discussed.